\(A=\dfrac{\sqrt{x}+1}{\sqrt{x}-3}=\dfrac{\sqrt{x}-3+4}{\sqrt{x}-3}=1+\dfrac{4}{\sqrt{x}-3}\)
A nguyên khi và chỉ khi:
\(\sqrt{x}-3\inƯ_4=\left\{\pm1;\pm2;\pm4\right\}\)
\(\Leftrightarrow\sqrt{x}\inƯ_4=\left\{1;2;4;5;7\right\}\)
\(\Leftrightarrow x\inƯ_4=\left\{1;4;16;25;49\right\}\)
Để \(\dfrac{\sqrt{x}+1}{\sqrt{x}-3}\) là số nguyên thì \(\sqrt{x}+1⋮\sqrt{x}-3\)
\(\Leftrightarrow\sqrt{x}-3\in\left\{1;-1;2;-2;4\right\}\)
\(\Leftrightarrow\sqrt{x}\in\left\{4;2;5;1;7\right\}\)
hay \(x\in\left\{16;4;25;1;49\right\}\)